Selection Approach to Identify the Optimal Biomarker Using Quantitative Muscle MRI and Functional Assessments in Becker Muscular Dystrophy. (3rd August 2021) - van de Velde, Nienke M.; Hooijmans, Melissa T.; Sardjoe Mishre, Aashley S.D.; Keene, Kevin R.; Koeks, Zaïda; Veeger, Thom T.J.; Alleman, Iris; van Zwet, Erik W.; Beenakker, Jan-Willem M.; Verschuuren, Jan J.G.M.; Kan, Hermien E.; Niks, Erik H.
Abstract : Objective: To identify the best quantitative fat–water MRI biomarker for disease progression of leg muscles in Becker muscular dystrophy (BMD) by applying a stepwise approach based on standardized response mean (SRM) over 24 months, correlations with baseline ambulatory tests, and reproducibility. Methods: Dixon fat–water imaging was performed at baseline (n = 24) and 24 months (n = 20). Fat fractions (FF) were calculated for 3 center slices and the whole muscles for 19 muscles and 6 muscle groups. Contractile cross-sectional area (cCSA) was obtained from the center slice. Functional assessments included knee extension and flexion force and 3 ambulatory tests (North Star Ambulatory Assessment [NSAA], 10-meter run, 6-minute walking test). MRI measures were selected using SRM (≥0.8) and correlation with all ambulatory tests (ρ ⩽ −0.8). Measures were evaluated based on intraclass correlation coefficient (ICC) and SD of the difference. Sample sizes were calculated assuming 50% reduction in disease progression over 24 months in a clinical trial with 1:1 randomization. Results: Median whole muscle FF increased between 0.2% and 2.6% without consistent cCSA changes. High SRMs and strong functional correlations were found for 8 FF but no cCSA measures. All measures showed excellent ICC (≥0.999) and similar SD of the interrater difference. Whole thigh 3 center slices FF was the best biomarker (SRM 1.04, correlations ρ ⩽ −0.81, ICC 1.00, SD 0.23%, sample size 59) based on low SD and acquisition and analysis time. Conclusion: In BMD, median FF of all muscles increased over 24 months. Whole thigh 3 center slices FF reduced the sample size by approximately 40% compared to NSAA.